COMPARISON OF NATIONAL EARLY WARNING SCORE (NEWS) AND REVISED TRAUMA SCORE (RTS) IN THE OUTCOME PREDICTION OF HEAD INJURY PATIENTS - Iseu Mapagresuka; Abdurahman Wahid; Ifa Hafifah (Journal of Nursing Science Update (JNSU), 2019)
Head injury is a global problem with mortality and morbidity outcome of 90%. One of the factors that infuence the outcome is the physiological status that can be assessed by using NEWS and RTS as simple validated assessments to predict outcome. This study aimed to compare NEWS and RTS in the outcome prediction of head injury patients. This study used an analytic observational method with prospective cohort design and consecutive sampling technique type in 48 head injured patients at Emergency Room of Ulin Banjarmasin Hospital, Idaman Banjarbaru Hospital, and Ratu Zalecha Martapura Hospital conducted from November 2017 to January 2018. Based on this study, the average age of head injury patients was 35.54 years, male, caused by traffic accidents, and 87.5% of people had living outcomes. Statistical analysis with a diagnostic test revealedthat NEWS accuracy in the outcome prediction of head injury patients had AUC value of 0.911, p<0.001 with 83.33% sensitivity and 83.33% specificity. RTS accuracy analysis in the outcome prediction of head injury patients had AUC value of 0.879, p = 0,001 with 83,33% sensitivity and 92,86%specificity. RTS was excelled and more able to predict the outcome of head injury patients compared to NEWS.